RELASI BUDAYA DAN AGAMA DALAM PERNIKAHAN - Luthfiyah Luthfiyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
Marriage in Islam view is a blessed treaty between a man and a woman to be halal. The aim of marriage is to proliferate and perpetuate the human life. The marriage tradition in each place is different. The understanding of relation between culture and religion still cannot be separated from the normative understanding of religion itself. It is the religion in form of prohibitions and orders.